The rescue - Rue, Nancy N. (Colorado Springs, Colo. : Focus on the Family Pub., 1995)
Josiah and Hope, two young Puritans living in Salem Village in 1689, befriend a Quaker woman and a Wampanoag Indian who are not accepted members of the community.
Keywords: Puritans; Christian life